1999
DOI: 10.1074/jbc.274.53.38155
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate d-Glucosaminyl 3-O-Sulfotransferase-3A SulfatesN-Unsubstituted Glucosamine Residues

Abstract: 3-O-Sulfation of glucosamine by heparan sulfate D-glucosaminyl 3-O-sulfotransferase (3-OST-1) is the key modification in anticoagulant heparan sulfate synthesis.However, the heparan sulfates modified by 3-OST-2 and 3-OST-3A, isoforms of 3-OST-1, do not have anticoagulant activity, although these isoforms transfer sulfate to the 3-OH position of glucosamine residues. In this study, we characterize the substrate specificity of purified 3-OST-3A at the tetrasaccharide level. The 3-OST-3A enzyme was purified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(150 citation statements)
references
References 45 publications
7
142
0
1
Order By: Relevance
“…The enzymes were purified by using heparin-Toyopearl and 3Ј,5Ј-ADP-agarose chromatographies as described previously (11,22). [ 35 S]PAPS was prepared by incubating 0.4 mCi/ml [ 35 S]Na 2 SO 4 (carrier-free, ICN) and 16 mM ATP with 5 mg/ml dialyzed yeast extract (Sigma) (12).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The enzymes were purified by using heparin-Toyopearl and 3Ј,5Ј-ADP-agarose chromatographies as described previously (11,22). [ 35 S]PAPS was prepared by incubating 0.4 mCi/ml [ 35 S]Na 2 SO 4 (carrier-free, ICN) and 16 mM ATP with 5 mg/ml dialyzed yeast extract (Sigma) (12).…”
Section: Methodsmentioning
confidence: 99%
“…The 3-O-sulfated HS is generated by 3-OST-3, but not by 3-OST-1. It should be noted that 3-OST-3-modified HS is rarely found in HS from natural sources, suggesting that HSV-1 recognizes a unique saccharide structure (11). In addition, a biochemical study revealed that 3-O-sulfated HS provides binding sites for HSV-1 envelope glycoprotein gD, which is a key viral protein involved in entry of HSV-1.…”
Section: -O-sulfotransferase Isoform 3 (3-ost-3) and It Provides Bimentioning
confidence: 99%
See 3 more Smart Citations